2007
DOI: 10.1063/1.2771161
|View full text |Cite
|
Sign up to set email alerts
|

Universality in eight-arm star polystyrene and methylcyclohexane mixtures near the critical point

Abstract: Measurements of the coexistence curve and turbidity were made on different molecular mass samples of the branched polymer-solvent system eight-arm star polystyrene in methylcyclohexane near its critical point. We confirmed that these systems belong in the Ising universality class. The location of the critical temperature and composition as well as the correlation length, susceptibility, and coexistence curve amplitudes were found to depend on molecular mass and the degree of branching. The coexistence curve di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
(77 reference statements)
0
11
1
Order By: Relevance
“…In other words, the solubility of star polymers becomes better with increasing arm number if the total molecular weight is the same. We note that, if Â=T c is plotted against M w À1=2 , the literature data for eight-arm star PS in methylcyclohexane 6,8 come much higher than the present data.…”
Section: Phase Diagramcontrasting
confidence: 47%
See 1 more Smart Citation
“…In other words, the solubility of star polymers becomes better with increasing arm number if the total molecular weight is the same. We note that, if Â=T c is plotted against M w À1=2 , the literature data for eight-arm star PS in methylcyclohexane 6,8 come much higher than the present data.…”
Section: Phase Diagramcontrasting
confidence: 47%
“…[1][2][3][4][5][6] This cannot be explained by theories invoking the Flory-Huggins type 7 mean-field approximation, but at present, there exists no molecular theory that explains the phase behavior of branched molecules. Recent Monte Carlo simulation results also fail to describe the experimental data.…”
mentioning
confidence: 99%
“…It is important to note that, for polydisperse micelles that form coexisting liquid phases, the cloud points and the coexistence curves do not coincide. Koningsveld , has shown that for polydisperse systems: “As a rule, it is not allowed to identify a cloud-point curve with a bimodal (coexistence curve), nor the maximum in a cloud-point curve with a critical point.” This differs from a monodisperse system such as methanol and cyclohexane or even from a polymer of narrow polydispersity in a solvent, where the onset of phase separationthe “cloud point”, where the system is opalescent as a second phase formscoincides with the coexistence curve. For monodisperse systems with an upper critical solution temperature (UCST) [or a lower critical solution point (LCST)], the maximum of the cloud point curve is also the maximum [or minimum] of the coexistence curve and is the critical point …”
Section: Introductionmentioning
confidence: 99%
“…1,5 Because of the polydispersity of the copolymer, the cloud point curve is not the same as the coexistence curve in this system. 5,13 This differs from a monodisperse system such as a polymer of narrow polydispersity in a solvent, 14 or methanol and cyclohexane, 15 in which the opalescence due to the onset of phase separationthe "cloud point"-coincides with the coexistence curve. This distinction is discussed in some detail by Huff et al, 5 who measured the micellization line, coexistence curves, and the cloud point curve in 17R4/H 2 O as shown in Fig.…”
Section: Phase Boundaries and Critical Pointmentioning
confidence: 99%
“…The cloudy and clear regions can be measured by the turbidity τ, which is an extinction coefficient for a transmitted beam of light that enters the sample of length L with an intensity I 0 and exits with an intensity I t : τ = −(1/L) ln(I t /I 0 ). 14 Using a measurement technique described previously, 14 we can illustrate the cloudiness for one composition of 17R4 and water in Fig. 2.…”
Section: E Turbiditymentioning
confidence: 99%